Measuring labour market transitions of youths in Thailand: Evidence from rotation groups (2012-21) in the Labour Force Surveys - Joshua D. Hawley; Nuttanan Wichitaksorn (International Labour Organization (ILO), 2024)
Using data from Thailand's Labour Force Survey from 2012 to 2021, the differences over time were investigated for the likelihood of youths moving between employment states, such as unemployment, employment and out of the labour force. Additional transitions were calculated for groups moving between vulnerable and non-vulnerable employment and with respect to education level and part- or full-time work. This analysis is useful to understand trends in the Thai labour force and showcase a unique method using panel data with national-level surveys from the National Statistical Office.
Keywords: 330; employment; youth employment; labour market; youth; labour force survey